Implementation of Web based Civil Administration System for Citizen Unit Level - Budhi Irawan; Purba Daru Kusuma; Rifqi Muhammad Fikri; Muhammad Riyadhul Jinan Nasution; Faiq Haqqani; Raenaldi Ardiansyah Sidik (Jurnal Abdimas, 2026)
Civil administration system is an important system that supports e-government to improve the governance process. Unfortunately, many citizen-unit level in Indonesia still handle this process manually.  This condition also happens in citizen unit no. 25, Melong Village, Cimahi, West Java. To solve this problem, a community service project by Telkom University is running to develop and implement the civil administration system for this citizen-unit. The community service team consists of lecturers and students. The system is developed based on web so that it can be accessed easily for the citizens. This system is also a mobile-friendly application so that the appearance is appropriate when it is accessed through smartphone. The main features are the demographic and financial data. The socialization was held on June 5, 2026. There are several issues regarding privacy, security, server, and additional features. All these issues have been addressed. To maintain the sustainability of the program, commitment for continuous improvement and implementation has been stated through capstone project, and submission for next funding.